Hope Family Program : Can It Reduce Poverty and Increase Welfare in Indonesia? - Dela Resina; Neng Kamarni; Febriandi Prima Putra (Jurnal Ekonomi Pembangunan, 2022)
The ultimate goal of development in developing countries is to reduce poverty that can be achieved through increasing welfare. Poverty is a multidimensional phenomenon that become a major challenge in all countries. To reduce poverty and increase community welfare, government intervention programs are needed. One of them is through the provision of cash assistance. The Conditional Cash Transfer program has been widely implemented in some countries. In Indonesia, this program is called the Family Hope Program (PKH). This cash transfer program has a lot of debate as an anti-poverty program. This research wants to see the impact of PKH on reducing poverty and increasing welfare in Indonesia. It used raw data from Susenas and analyzed by SEM-PLS method. The results of this research show that PKH has a negative-significant effect on poverty and a positive-significant impact on welfare in Indonesia. In addition, the results of the analysis also show that poverty has a negative-significant influence on people's welfare in Indonesia.